A Descriptive Study to Assess Knowledge Regarding Antenatal Care among Pregnant Women at District Hospital Gopeshwar, Chamoli in View to Develop Pamphlets - Negi, Meena; Anjali, K. M.; Pokhriyal, Anjali; Nand Nautiyal, Krishna; Pant, Monika; Rana, Sonam (Indian Journal of Nursing Sciences, 2024)
Aim: The aim of conducting the study was to improve knowledge of pregnant women regarding antenatal care (ANC). Materials and Methods: Non-experimental (descriptive) research design was adopted for this study and total 100 samples were selected using non-probability convenient sampling technique. The structured questionnaire regarding ANC was prepared and used to data collection. The obtained data were analyzed and interpreted in terms of the objectives of the study. Non-experimental research design was adopted for the study that focuses on obtaining information regarding knowledge related to ANC. Descriptive and inferential statistics were used for data analysis. Results: The result shows that 21 (21%) pregnant women were having good knowledge, 53 (53%) pregnant women were having average knowledge, and 26 (26%) pregnant women had poor knowledge about ANC. Demographic variables such as age, education, occupation, and monthly income have significant influence on knowledge of antenatal women (P > 0.05) regarding ANC. The conclusion of this study was that majority of pregnant women have average knowledge about ANC and there is a need to improve their knowledge so that maternal as well as fetal mortality rate can be reduced. Conclusion: This study was that pregnant women had average knowledge regarding ANC and there is a need to improve their knowledge through educating them related to ANC.